2022
DOI: 10.3389/fonc.2022.864111
|View full text |Cite
|
Sign up to set email alerts
|

Modified Prostate Health Index Density Significantly Improves Clinically Significant Prostate Cancer (csPCa) Detection

Abstract: BackgroundEarly screening of clinically significant prostate cancer (csPCa) may offer opportunities in revolutionizing the survival benefits of this lethal disease. We sought to introduce a modified prostate health index density (mPHI) model using imaging indicators and to compare its diagnostic performance for early detection of occult onset csPCa within the prostate-specific antigen (PSA) gray zone with that of PHI and PHID.Methods and ParticipationBetween August 2020 and January 2022, a training cohort of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…19 However, contrasting findings have been reported on the ability of PHI and PHID to detect csPCa defined after radical prostatectomy. 20 In our study, PHID and p2PSA/fPSAD showed the highest AUC for csPCa defined with both classification (for csPCa as GG ≥ 2, AUC 0.737, 0.736; for csPCa as GG ≥ 3, AUC 0.668, 0.670, respectively), but did not significantly differ from that of PHI and p2PSA/fPSAratio (for csPCa as GG ≥ 2, p = 0.409, 0.180 and for csPCa as GG ≥ 3, p = 0.558, 0.087, respectively). Further studies on larger population are needed to better address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, contrasting findings have been reported on the ability of PHI and PHID to detect csPCa defined after radical prostatectomy. 20 In our study, PHID and p2PSA/fPSAD showed the highest AUC for csPCa defined with both classification (for csPCa as GG ≥ 2, AUC 0.737, 0.736; for csPCa as GG ≥ 3, AUC 0.668, 0.670, respectively), but did not significantly differ from that of PHI and p2PSA/fPSAratio (for csPCa as GG ≥ 2, p = 0.409, 0.180 and for csPCa as GG ≥ 3, p = 0.558, 0.087, respectively). Further studies on larger population are needed to better address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment strategy for patients with nonsignificant PCa includes watchful waiting and active surveillance, with only csPCa patients requiring curative treatment (10). Therefore, the screening of csPCa becomes an important part of the treatment strategy (15). Studies have shown that approximately 75% of patients undergo unnecessary prostate biopsies based on PSA values only (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…12 Besides, to reduce the potential bias caused by serological category indicators alone, more researchers have searched for extra serum-based indices or brought prostatic morphological parameters from TRUS or multiparametric magnetic resonance imaging to optimize prediction models, including serum cytokines, PSA density (PSAD), PSAD modified by prostate transition zone volume (PSATZD), PHID, modified PHI density (mPHID), and other multivariable predictive models. [13][14][15][16][17] Noteworthy, several studies have reported that incorporating the prostate transition zone volume (PTZV) as a supplementary component of a PSA-based predictive model can effectively decrease the number of unnecessary biopsies while simultaneously maintaining a high level of sensitivity in detecting PCa. 15,18,19 The tPSA, however, is more prostate organ-specific rather than cancerspecific and is often associated with peripheral zone (PZ) cancer rather than TZ hyperplasia.…”
Section: Evaluating the Role Of Morphological Parameters In The Prost...mentioning
confidence: 99%